Effect of Artemisia annua on anticoccidial action, intestinal microbiota and metabolites of Hu lambs - Shuaiqi Liu; Shiheng Li; Shuqi Cheng; Manyu Liu; Jing Li; Senyang Li; Xiaoying Li; Longxian Zhang; Fuchun Jian (BMC Veterinary Research)
Abstract Background Coccidia are among the primary pathogens causing diarrhea and even fatalities in lambs. With the increasing use of chemical drugs to treat coccidiosis, the problem of drug resistance is becoming more and more threatening. Therefore, there is an urgent need to identify novel alternative drugs for the treatment of the lamb coccidia. In this study, the effect of different doses and extraction methods of Artemisia annua (A. annua) on anticoccidial activity and growth performance was assessed by oocysts output (OPG), fecal index, average daily gain (ADG) and the new production value of experimental lambs. High-throughput sequencing technology was employed to investigate the effect of A. annua on the intestinal microbiota and metabolites of lambs afflicted with coccidiosis. Results The results revealed that all A. annua treatment groups exhibited good anticoccidial effects. According to the soft stool index and ADG analysis, the Low-dose A. annua (AL) and A. annua alcohol extract (AA) groups demonstrated a better overall effect. The microbiota and metabolites of lambs changed after A. annua was administered. Unclassified_Muribaculaceae exhibited a significant positive correlation with ADG (P < 0.05) and a negative correlation with OPG, although the latter was not statistically significant (P > 0.05). Alistipes displayed a significant negative correlation with ADG (P < 0.05), and a positive correlation with OPG (P > 0.05). Additionally, UCG 005 exhibited a highly significant negative correlation with OPG (P < 0.01). Conclusion The above results demonstrated that AL and AA groups had more effective anticoccidial action. Unclassified_Muribaculaceae could be employed as a suitable probiotic to enhance weight gain in lambs, while UCG-005 could inhibit intestinal Eimeria colonization in lambs. Alistipes may serve as a biomarker for predicting the risk of intestinal coccidia outbreaks in lambs. A. annua induced significant changes in gut microbiota, accompanied by corresponding changes in metabolites. These differences in gut microbiota and metabolites provide valuable insights for subsequent research on the mechanisms underlying anticoccidial action.